Crystallographic polarity effect of ZnO on thin film growth of pentacene. (13th March 2017) - Nakamura, Tatsuru; Nagata, Takahiro; Hayakawa, Ryoma; Yoshimura, Takeshi; Oh, Seungjun; Hiroshiba, Nobuya; Chikyow, Toyohiro; Fujimura, Norifumi; Wakayama, Yutaka
Abstract: The spontaneous polarization effect of ZnO on the thin film growth of pentacene, which is a typical π conjunction organic semiconductor, was investigated. Pentacene thin films were grown on polar ZnO surfaces by ultraslow organic film physical vapor deposition to obtain layer-by-layer growth. X-ray diffraction measurements revealed that pentacene molecules stand upright on polar ZnO surfaces, and that the films consist of two polymorphs, namely, the thin-film and bulk phases. The thin-film phases of pentacene were observed regardless of the polarity of the ZnO substrate at a thickness of less than six molecular layers. However, pentacene on a Zn-polar ZnO substrate gradually changed to the bulk phase unlike that on an O-polar ZnO substrate. Kelvin probe force microscopy measurements revealed that the surface potential of pentacene becomes more positive with increasing pentacene thickness at less than two molecular layers. The variation in the potential of pentacene on the Zn-polar ZnO substrate was larger than that of pentacene on the O-polar ZnO substrate. These findings indicate that the polarity of the semiconductor can control the growth and electronic state of the inorganic/organic semiconductor interface.